Contribution of Insurance on Economic Growth in India: An Econometric Approach - Mall, Sunita (Journal of Applied Business and Economics, 2018)
Insurance is an important part in the financial sector that contributes significantly to the economy of a country. Insurance market contributes hugely to the economic growth and also helps in managing risk more effectively. This piece of research work made an attempt to examine the relationship between insurance and economic growth in India considering the state level data and contributing to the existing literature. The data is collected for twenty-five states of India and covers the time period for 1995 to 2015. Endogenous growth model is used. Fixed effect model. Pooled ordinary least square generalized moment method (GMM) estimation techniques are used to establish the relationship between insurance and economic growth. This result infers that the insurance policies which can improve the insurance penetration in different states of India should be promoted. The relationship between physical capital and economic growth indicates that more investments should be made on infrastructure policies like health facilities, road etc. This research work could contribute largely to the insurance growth and economic growth and thus is beneficial to the Insurance sector and the Government of India.